2017
DOI: 10.1021/acs.jchemed.6b00590
|View full text |Cite
|
Sign up to set email alerts
|

Acid–Base Poker: A Card Game Introducing the Concepts of Acid and Base at the College Level

Abstract: A card game has been developed to illustrate acids and bases to first-year general chemistry students. The game offers an enjoyable method to practice categorizing acids and bases. In this game, which is adapted from Texas Hold'em, a player uses his/ her knowledge of the properties of acids and bases to try to make the highest possible rank with five cards. The game can be used as a method to engage students at an early stage of chemical education, providing a different perspective from the textbook and a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
(11 reference statements)
1
15
0
4
Order By: Relevance
“…They are already available commercially or published as research materials, for examples video games, android application, modified poker games, card games, and board games [3][4][5][6]. The games in chemistry provide an efficient and fun alternative to more forms of education [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are already available commercially or published as research materials, for examples video games, android application, modified poker games, card games, and board games [3][4][5][6]. The games in chemistry provide an efficient and fun alternative to more forms of education [4].…”
Section: Introductionmentioning
confidence: 99%
“…The games in chemistry provide an efficient and fun alternative to more forms of education [4]. It can be used as a method to engage students at an early stage of chemical education, providing a different perspective from the textbook, and an effective and entertaining way to help college students learn some aspects of general chemistry [6]. Furthermore, games also allow the student to play an active role in the learning process [3].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating educational games into the undergraduate chemistry classroom has many potential benefits, including promoting engagement with the material, improving student learning, and providing alternative study strategies. Games reported for college-level chemistry and biochemistry courses take many forms, with common categories including computer simulations, card games, , drawing games, word games, and board games. , Educational chemistry games have been incorporated into a range of college-level courses, including nonmajor courses, , general chemistry, ,, organic chemistry, biochemistry, ,, and analytical courses. , These recent examples are not meant to be an exhaustive list, but the breadth of those cited here suggests that there are many opportunities to design and adapt games for educational purposes.…”
mentioning
confidence: 99%
“…Educational games are commonly used to help students cope with the challenges they encounter in the learning process. 7 Games are a useful pedagogical instrument that enables individuals to construct their knowledge in an entertaining and challenging environment. 2,8 Several studies have found that games are influential in the learning process.…”
mentioning
confidence: 99%
“…Games are a useful tool to assist with this problem. Educational games are commonly used to help students cope with the challenges they encounter in the learning process …”
mentioning
confidence: 99%